Pengaruh Strategi Pembelajaran Inquiry Terbimbing Terhadap Kemampuan Berpikir Kritis Siswa pada Materi Ekosistem - Nursina, Desi; Nursa'ban, Eva; Ewisahrani, Ewisahrani (STKIP HARAPAN BIMA, 2025)
This study aims to analyze the effect of guided inquiry learning strategies on students' critical thinking skills in ecosystem material at SMP Negeri 3 Wera. The research design used was a quasi-experimental design with a non-equivalent control group involving pretest and posttest in both the experimental and control groups. The data collection technique was carried out by distributing instruments in the form of critical thinking essay tests (pretest post-test) and observation sheets for student and teacher activities during the learning process. The data analysis technique used the Kolmogorov-Smirnov normality test and Levene's homogeneity test as prerequisite tests, then hypothesis testing (t-test) and N-gain to see the comparison between the pretest and post-test using SPSS-25.. The results showed that the critical thinking skills of students in the experimental group improved significantly compared to those in the control group. The N-Gain score of the experimental group was categorized as moderate, while the control group was categorized as low. The guided inquiry learning strategy effectively encouraged students to actively identify problems, develop hypotheses, collect data, and draw conclusions independently. This learning model can be applied effectively even in schools with limited resources.